Crossing ditch for reconfigurable planetary robots - 张力平 马书根 李斌 张国伟 张政 曹秉刚 (Journal of Shanghai University, 2006)
A new reconfigumble planetary robots system （RPRS） is introduced. The locomotion mechanism alld crossing ditch ability by negotiation among ckild-robots are analyzed. Three configurations are introduced and their characteristics for crossing ditch compared. In order to cross the ditch whose width is broader than the length of the triangle wheel＇ s edge, a novel method based on the locomotion mechanism of the child-robot is proposed. This makes the two leading robots hold the first robot together with their velocities in opposite directions. Statics for the reconfigurable robot group are analyzed. The result shows that the motors can supply sufficient force moment to cross channel. Simulation .experiments are carried out with VC and OPENGL.